To find the amount of change \( c \) that Mela receives, we can set up the equation based on the transaction. Mela gives the cashier $50 for a pair of shoes that costs $40.99. The equation that represents this situation is:
\[ c + 40.99 = 50 \]
This equation states that the amount of change \( c \) plus the cost of the shoes ($40.99) equals the amount Mela gave ($50).
To find \( c \), we can solve the equation:
\[ c = 50 - 40.99 = 9.01 \]
Thus, Mela receives $9.01 in change.
Therefore, the correct answer is: c + 40.99 = 50; Mela receives $9.01 in change.